Taking problem-solving courts to scale: diverse applications of the specialty court model - Ahlin, Eileen; Douds, Anne S. (Lexington Books, 2021)
Drug courts : the beginning of the movement by Cassandra Atkin-Plunk -- Mental health courts : policy and practice by Irina Fanarraga and Deborah Koetzle -- DWI courts by Carrie Petrucci -- Reentry courts by Lama Hassoun Ayoub and Michael Rempel -- Creating a home base for treatment in homelessness courts by Kyle C. Troeger and Anne S. Douds -- Juvenile dependency courts : goals and challenges of the adoption and Safe Families Act of 1997 by Mitra Z. Honardoost and Eileen M. Ahlin -- Community courts : restoring the community one case at a time by Tyrell Connor -- A trifecta of challenges for veterans treatment courts by Jared A. Michaels and Anne S. Douds -- Tribal healing to wellness courts by Elyshia Aseltine and Joan Lobo Antunes -- Seeking safety and accountability through domestic violence courts by Amanda B. Cissner and Rebecca Thomforde Hauser -- Restoring humanity through human trafficking courts by Anne S. Douds, Ella R. Warburton, and Kealy A. Cassidy -- Sex offense courts : a historical and international overview by Ashley Kilmer and Amanda Emmert -- Opioid intervention courts by Lisa Shannon, Monica Himes, Shondrah Nash, and Jennifer Newell -- Conclusion.